Features of the level regime of the Gorky and Cheboksary reservoirs in the spring-summer period and their effect on fish spawning - Lyudmila M. Minina; Aleksander E. Minin (Водное хозяйство России: проблемы, технологии, управление)
Th e article compares the features of the level regime of the Gorky and Cheboksary reservoirs during the spawning period of fi sh and analyzed their influence on the various aspects of natural reproduction of commercial fi sh species.